A hydrogel electrolyte, preparation method and application

By using PVA/PSBMA hydrogel electrolyte in zinc-air batteries, the ion dialysis and balance between hydrogel and electrolyte is achieved through immersion, the problem of poor conductivity of traditional hydrogels is solved, and the zinc-air battery is realized Efficient transmission of ions and battery stability and flexibility.

CN115172947BActive Publication Date: 2025-02-21XI'AN POLYTECHNIC UNIVERSITY
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202210912321.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-07-29
Publication Date
2025-02-21
Estimated Expiration
2042-07-29

AI Technical Summary

Technical Problem

Traditional hydrogels have poor mechanical properties and poor conductivity, making it difficult to provide conductive paths for ion transmission in zinc-air batteries, resulting in an increased risk of safety accidents.

Method used

Using PVA/PSBMA hydrogel electrolyte, the ion dialysis and equilibrium of hydrogel and electrolyte is achieved by soaking in dimethyl sulfoxide and aqueous solution of potassium hydroxide and zinc acetate to form a semi-interpenetrating network structure to improve conductivity and mechanical properties.

Benefits of technology

The uniform distribution and efficient transmission of ions in zinc-air batteries are achieved, the flexibility and electrochemical stability of the battery are improved, and the risks of electrolyte volatilization and leakage are reduced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115172947B_ABST
    Figure CN115172947B_ABST
Patent Text Reader

Abstract

The present invention discloses a hydrogel electrolyte, a preparation method and an application, and belongs to the field of batteries. A preparation method of a hydrogel electrolyte of the present invention adopts immersion to obtain a hydrogel electrolyte. During the immersion process, ions undergo dialysis so that the hydrogel and the electrolyte finally reach an ion equilibrium state. At this time, the ions inside the hydrogel are evenly distributed in the polymer network and channels, which is beneficial to the ion migration during the battery charging and discharging process. An application of a hydrogel electrolyte of the present invention, as an electrolyte in a zinc-air battery, the hydrogel electrolyte has a high conductivity and stability based on physical crosslinking and dynamic crosslinking of zwitterions, and provides good flexibility and electrochemical stability for the zinc-air battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of batteries, and in particular to a hydrogel electrolyte, a preparation method and an application thereof. Background Art

[0002] In the context of the intelligent era, the craze for flexible electronic devices is rapidly updating. The emergence of flexible watches, mobile phones and other electronic devices has made flexible energy storage devices one of the most promising research directions. Due to its abundant reserves in nature, low cost, environmental friendliness, and fast electrochemical reaction kinetics, zinc is one of the candidate materials for flexible batteries. Although zinc-air batteries have a high theoretical energy density (1084Wh·kg -1 ), but the electrolyte is prone to volatilization or leakage during use, causing safety accidents. For this reason, the study selected semi-solid hydrogel soft materials between liquid and solid as electrolytes. However, traditional hydrogels have poor mechanical properties and poor conductivity, making it difficult to provide a conductive path for ion transport in batteries. Therefore, developing a gel electrolyte with good flexibility and excellent ion transport capacity has scientific research value that cannot be ignored. Summary of the invention

[0003] The purpose of the present invention is to overcome the disadvantages of the prior art and provide a hydrogel electrolyte, a preparation method and an application thereof.

[0004] In order to achieve the above object, the present invention adopts the following technical solutions:

[0005] A method for preparing a hydrogel electrolyte comprises the following steps:

[0006] The PVA / PSBMA hydrogel is immersed in a dimethyl sulfoxide and aqueous solution of potassium hydroxide and zinc acetate, and the immersion is completed to obtain a PVA / PSBMA hydrogel polymer electrolyte.

[0007] Further, in a dimethyl sulfoxide and aqueous solution of potassium hydroxide and zinc acetate, the volume ratio of dimethyl sulfoxide to water is 1:4;

[0008] The concentration of potassium hydroxide is 6 mol / L, and the concentration of zinc acetate is 0.2 mol / L.

[0009] Furthermore, the soaking time is more than 24 hours.

[0010] Further, the PVA / PSBMA hydrogel is synthesized by the following synthesis method:

[0011] Dissolve polyvinyl alcohol in water to obtain solution A;

[0012] The SBMA monomer is dissolved in water to obtain solution B, then solution A and solution B are mixed, an initiator and a cross-linking agent are added to obtain a prepolymer solution, and then a polymerization reaction is carried out to obtain a PVA / PSBMA hydrogel;

[0013] The polymerization reaction temperature is 80-90°C and the time is 8-12 hours.

[0014] Further, the initiator is potassium persulfate;

[0015] The cross-linking agent is N,N'-methylenebisacrylamide.

[0016] Further, the concentration of polyvinyl alcohol was 0.2 g / mL;

[0017] The mass ratio of SBMA monomer to polyvinyl alcohol is (1-3):2;

[0018] The mass of the initiator is 0.2% of the mass of the SBMA monomer;

[0019] The mass of the cross-linking agent is 0.2% of the mass of the SBMA monomer.

[0020] A hydrogel electrolyte is prepared according to the preparation method of the present invention.

[0021] Furthermore, the liquid absorption rate is 317% to 439%.

[0022] Application of the hydrogel electrolyte of the invention in zinc-air batteries.

[0023] Furthermore, a zinc sheet is used as an anode, a hydrogel electrolyte is used as an electrolyte, and a carbon cloth loaded with a Pt / C catalyst is used as an air cathode. The anode, electrolyte, and cathode are assembled into a sandwich structure and then packaged to obtain a zinc-air battery.

[0024] Compared with the prior art, the present invention has the following beneficial effects:

[0025] The invention discloses a method for preparing a hydrogel electrolyte, which obtains the hydrogel electrolyte by immersion. During the immersion process, ions undergo dialyzation so that the hydrogel and the electrolyte finally reach an ion equilibrium state. At this time, the ions inside the hydrogel are evenly distributed in the polymer network and channels, which is beneficial to the ion migration during the battery charging and discharging process.

[0026] Furthermore, a one-step freeze-thaw cycle method was used to synthesize the hydrogel, which is simple and convenient.

[0027] A hydrogel electrolyte of the present invention, in a PVA / PSBMA semi-interpenetrating network hydrogel, PVA chains are physically cross-linked to form hydrogen bonds, and PSBMA chains generate dynamic electrostatic interactions. When the gel is deformed, the synergistic effect of the two gives the gel electrolyte recoverability, thereby having excellent mechanical properties. The zwitterionic groups in the PSBMA structure form a continuous ion cross-linked network, and SBMA forms a polymer chain (quaternary ammonium cation and sulfonic acid anion) with anions and cations on the side groups after polymerization. The ions on the chain move to form a continuous conductive network and ion channel, which is beneficial to the transmission of hydroxide ions during the battery charging and discharging process, and realizes ionic conductivity. On the other hand, DMSO is introduced into the electrolyte to form hydrogen bonds with water molecules, inhibiting the interaction of water molecules with each other, and avoiding the positive terminal of the zinc-air battery being exposed to the air to cause the electrolyte to lose water and cause performance degradation.

[0028] The application of a hydrogel electrolyte of the present invention, as an electrolyte in a zinc-air battery, has high conductivity and stability based on physical crosslinking and dynamic crosslinking of zwitterions, provides good flexibility and electrochemical stability for the zinc-air battery, specifically, potassium hydroxide (hydroxyl ions) provides hydroxide ions for the normal operation of the battery, participates in the electrochemical charge and discharge reaction, dimethyl sulfoxide and the binary solvent of water have good polarity, inhibit the hydrogen bond interaction between water molecules by combining with water molecules, and the addition of zinc acetate (zinc ions) improves the negative electrode zinc dendrite problem caused by uneven electric field distribution during the charge and discharge process of the battery, thereby improving the battery stability. Tests show that the battery has good stability during the cycle process, no obvious mutation occurs within 30 hours, the voltage window is small, and no fluctuation state occurs. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] Figure 1 The tensile properties of the gel electrolytes obtained in Examples 1 and 2 and the comparative example are shown;

[0030] Figure 2 The liquid absorption rate diagram of the gel electrolyte obtained in Examples 1 and 2 and the comparative example;

[0031] Figure 3 This is the polarization curve diagram of the zinc-air battery obtained in Example 4;

[0032] Figure 4 This is the charge and discharge cycle diagram of the zinc-air battery obtained in Example 4. DETAILED DESCRIPTION

[0033] In order to enable those skilled in the art to better understand the scheme of the present invention, the technical scheme in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work should fall within the scope of protection of the present invention.

[0034] It should be noted that the terms "first", "second", etc. in the specification and claims of the present invention and the above-mentioned drawings are used to distinguish similar objects, and are not necessarily used to describe a specific order or sequence. It should be understood that the data used in this way can be interchanged where appropriate, so that the embodiments of the present invention described herein can be implemented in an order other than those illustrated or described herein. In addition, the terms "including" and "having" and any variations thereof are intended to cover non-exclusive inclusions, for example, a process, method, system, product or device that includes a series of steps or units is not necessarily limited to those steps or units that are clearly listed, but may include other steps or units that are not clearly listed or inherent to these processes, methods, products or devices.

[0035] The present invention is further described in detail below in conjunction with the accompanying drawings:

[0036] Example 1

[0037] Dissolve 2 g of PVA in 10 mL of deionized water, heat and stir at 95 °C for 30 min to obtain a clear and transparent solution, and let it stand to remove bubbles;

[0038] 1 g of SBMA was dissolved in 10 mL of deionized water, and stirred at room temperature for 10 min on a magnetic stirrer. The PVA solution after standing to remove bubbles was then mixed with the SBMA solution. 0.002 g of initiator (KPS) and 0.002 g of cross-linking agent (MBAA) were added to obtain a mixed solution. The mixed solution was heated and stirred at 80° C. for 12 h, and then stood to remove bubbles for 10 min.

[0039] After the bubbles were completely eliminated, the solution was injected into the mold with a syringe, frozen at -40°C for 3 h, and thawed at room temperature for 1 h to obtain the PVA / PSBMA hydrogel.

[0040] Example 2

[0041] Dissolve 2 g of PVA in 10 mL of deionized water, heat and stir at 95 °C for 30 min to obtain a clear and transparent solution, and let it stand to remove bubbles;

[0042] 3 g of SBMA was dissolved in 10 mL of deionized water, and stirred at room temperature for 10 min on a magnetic stirrer. The PVA solution after standing to remove bubbles was then mixed with the SBMA solution, and 0.006 g of initiator (KPS) and 0.006 g of cross-linking agent (MBAA) were added to obtain a mixed solution. The mixed solution was heated and stirred at 90° C. for 8 h, and then stood to remove bubbles for about 10 min.

[0043] After the bubbles were completely eliminated, the solution was injected into the mold with a syringe, frozen at -40°C for 3 h, and thawed at room temperature for 1 h to obtain PVA / PSBMA hydrogel.

[0044] Example 3

[0045] Dissolve 2 g of PVA in 10 mL of deionized water, heat and stir at 95 °C for 30 min to obtain a clear and transparent solution, and let it stand to remove bubbles;

[0046] 2 g of SBMA was dissolved in 10 mL of deionized water, and stirred at room temperature for 10 min on a magnetic stirrer. The PVA solution after standing to remove bubbles was then mixed with the SBMA solution, and 0.004 g of initiator (KPS) and 0.004 g of cross-linking agent (MBAA) were added to obtain a mixed solution. The mixed solution was heated and stirred at 85° C. for 8 h, and then stood to remove bubbles for about 10 min.

[0047] After the bubbles were completely eliminated, the solution was injected into the mold with a syringe, frozen at -40°C for 3 h, and thawed at room temperature for 1 h to obtain PVA / PSBMA hydrogel.

[0048] Comparative Example

[0049] Dissolve 2g of polyvinyl alcohol in 10mL of deionized water, heat and stir at 95°C for 30min to obtain a clear and transparent solution, let it stand for 10min to remove bubbles, and inject the solution into the mold with a syringe after the bubbles are completely eliminated. Freeze at -40°C for 3h and thaw at room temperature for 1h to obtain PVA hydrogel.

[0050] Tensile performance test: The hydrogels obtained in Example 1, Example 2 and the comparative example were subjected to tensile performance tests respectively. The dimensions of the tensile specimens were: original gauge length 15 mm, thickness 1.3 mm, width 2 mm. The tensile properties of the gel electrolytes obtained in Example 1, Example 2 and the comparative example were shown in FIG. Figure 1The tensile stress of the gel in Example 1 at a strain of 290% is 0.6MPa, the tensile stress of the gel in Example 2 at a strain of 602% is 0.7MPa, and the tensile stress of the gel in the comparative example at a strain of 350% is 0.09MPa. The mechanical properties of PVA hydrogel are poor, the network is loose, and the liquid absorption rate is large. After adding 5wt% SBMA, the gel has a semi-interpenetrating structure, the network is dense, the PVA chain and the PSBMA chain are intertwined to form physical crosslinks, and PSBMA forms zwitterionic dynamic crosslinks, the mechanical properties are improved, and the liquid absorption rate is reduced. After adding 15wt% SBMA, the network density of the gel is better, the dynamic ions are richer, and the breaking stress and elongation at break are improved at the same time, so that the gel has excellent liquid absorption rate and mechanical properties.

[0051] The liquid absorption rate of the gel electrolyte was tested. After freeze-drying the hydrogels obtained in Example 1, Example 2 and the comparative example, they were immersed in 6 mol / L potassium hydroxide and 0.2 mol / L zinc acetate electrolyte, weighed in real time, and the changes in the liquid absorption rate were recorded. The liquid absorption rate of the gel electrolyte was shown in FIG. Figure 2 The liquid absorption rate of the hydrogel in the comparative example is 438%, the liquid absorption rate of the hydrogel in Example 1 is 317%, and the liquid absorption rate of the hydrogel in Example 2 is 439%.

[0052] Example 4

[0053] (1) The PVA / PSBMA hydrogel of Example 2 was placed in an electrolyte solution of 6 mol / L potassium hydroxide, 0.2 mol / L zinc acetate, and dimethyl sulfoxide (DMSO: H 2 O=1:4) for 24h to obtain a PVA / PSBMA hydrogel polymer electrolyte;

[0054] (2) The flexible zinc-air battery is manufactured as a sandwich structure by layer-by-layer assembly method

[0055] Zinc sheet (10×30mm 2 , thickness 0.5mm) was polished with sandpaper, cleaned and dried as anode;

[0056] The Pt / C catalyst was coated on carbon cloth as the air cathode;

[0057] Then take the PVA / PSBMA composite hydrogel polymer electrolyte (10×20mm 2 ) is placed between the zinc sheet and an air electrode of the same size;

[0058] Finally, the assembled air battery was packaged with a breathable bandage, and the battery polarization performance test and constant current cycle charge and discharge test were carried out.

[0059] See also Figure 3 , Figure 3This is the polarization curve of the zinc-air battery obtained in Example 4. It can be seen that the discharge polarization curve of the battery containing the hydrogel electrolyte has a stable decreasing trend, and the power density peak reaches 96mW·cm -2

[0060] See also Figure 4 , Figure 4 This is the charge and discharge cycle diagram of the zinc-air battery obtained in Example 4. It can be seen that the battery has good charge and discharge cycle stability, a small charge and discharge interval, and can work continuously for about 30 hours.

[0061] The results show that the Zn-air battery assembled with gel electrolyte containing 15wt% SBMA has excellent polarization performance and charge-discharge cycle performance. The voltage decreases slowly with the increase of current, and the power density is the highest, reaching 96mW·cm -2 , the charge and discharge cycle can be about 30h.

[0062] The above contents are only for explaining the technical idea of ​​the present invention and cannot be used to limit the protection scope of the present invention. Any changes made on the basis of the technical solution in accordance with the technical idea proposed by the present invention shall fall within the protection scope of the claims of the present invention.

Claims

1. A method for preparing a hydrogel electrolyte, characterized in that: The following steps are involved: The PVA / PSBMA hydrogel is immersed in a dimethyl sulfoxide and aqueous solution of potassium hydroxide and zinc acetate, and the immersion is completed to obtain a PVA / PSBMA hydrogel polymer electrolyte.

2. The method for preparing a hydrogel electrolyte according to claim 1, characterized in that: In the dimethyl sulfoxide and aqueous solution of potassium hydroxide and zinc acetate, the volume ratio of dimethyl sulfoxide to water is 1:4; The concentration of potassium hydroxide is 6 mol / L, and the concentration of zinc acetate is 0.2 mol / L.

3. The method for preparing a hydrogel electrolyte according to claim 1, characterized in that: The soaking time is more than 24 hours.

4. The method for preparing a hydrogel electrolyte according to claim 1, characterized in that: The PVA / PSBMA hydrogel is synthesized by the following synthesis method: Dissolve polyvinyl alcohol in water to obtain solution A; The SBMA monomer is dissolved in water to obtain solution B, then solution A and solution B are mixed, an initiator and a cross-linking agent are added to obtain a prepolymer solution, and then a polymerization reaction is carried out to obtain a PVA / PSBMA hydrogel; The polymerization reaction temperature is 80-90°C and the time is 8-12 hours.

5. The method for preparing a hydrogel electrolyte according to claim 4, characterized in that: The initiator is potassium persulfate; The cross-linking agent is N,N'-methylenebisacrylamide.

6. The method for preparing a hydrogel electrolyte according to claim 4, characterized in that: The concentration of polyvinyl alcohol was 0.2 g / mL; The mass ratio of SBMA monomer to polyvinyl alcohol is (1-3):2; The mass of the initiator is 0.2% of the mass of the SBMA monomer; The mass of the cross-linking agent is 0.2% of the mass of the SBMA monomer.

7. A hydrogel electrolyte prepared according to the preparation method according to any one of claims 1 to 6.

8. The hydrogel electrolyte according to claim 7, characterized in that The liquid absorption rate is 317% to 439%.

9. Use of the hydrogel electrolyte according to claim 7 or 8 in a zinc-air battery.

10. Application of the hydrogel electrolyte in zinc-air batteries according to claim 9, characterized in that: A zinc sheet is used as an anode, a hydrogel electrolyte is used as an electrolyte, and a carbon cloth loaded with a Pt / C catalyst is used as an air cathode. The anode, electrolyte, and cathode are assembled into a sandwich structure and then packaged to obtain a zinc-air battery.

Citation Information

Patent Citations

  • Preparation method of three-dimensional interconnected multistage macroporous structure gel polymer electrolyte

    CN114773627A

  • Grafted copolymer, prepraring method thereof, and polymer electrolyte membrane comprising the grafted copolymer

    KR102254908B1